Development of Conceptual Framework to Understand Factors Associated with Return to Work among Cancer Survivors: A System¬atic Review - Sze Loon CHOW; Anselm Su TING; Tin Tin SU (Tehran University of Medical Sciences, 2014)
This systematic review was conducted to develop a conceptual framework that addresses various factors associated with return to work among cancer survivors. Databases Medline, EMBASE, ProQuest, PubMed and ScienceDirect were systematically searched using medical subject headings [MeSH] for studies published in English from 1990 to 2013. Studies that described adult cancer patients' self-reported data or patients' point of view on factors associated with return to work or employment status following cancer diagnosis were included. Articles selection was conducted in three steps: selection based on title and abstract, retrieval of full text and additions of articles from reference lists and recommendations from experts. Disagreement in data extraction was solved by consultation of third reviewer. Out of twenty seven articles, breast cancer was the most studied type of cancer (30%) while colorectal cancer was studied independently in two articles (7.4%). Conceptual framework on return to work identifies factors under environmental, personal, work demand, work ability, health status and financial factors. Extensive search of scientific databases over last 24 years and the development of the conceptual framework are the strength of this review. Conceptual framework reveals the various factors including non-medical factors associated with return to work upon cancer diagnosis. It serves as a reminder to the policy makers to focus on modifiable factors as potential areas for intervention to assist cancer survivors return to work, especially those with little financial assistance and health insurance.